2002
DOI: 10.1029/2001jd000587
|View full text |Cite
|
Sign up to set email alerts
|

ATMOS version 3 water vapor measurements: Comparisons with observations from two ER‐2 Lyman‐α hygrometers, MkIV, HALOE, SAGE II, MAS, and MLS

Abstract: [1] We have compared a new version of Atmospheric Trace Molecule Spectroscopy Experiment (ATMOS) retrievals (version 3) of stratospheric and mesospheric water vapor with observations from shuttleborne, satelliteborne, balloonborne, and aircraftborne instruments. These retrievals show agreement to within 5% with the MkIV observations in the middle and lower stratosphere. ATMOS agrees with the National Oceanic and Atmospheric Administration (NOAA) Lyman-a hygrometer to within 5% except for features with spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Since both SAGE II and HALOE are carried on inclined-orbit satellites, occultation events are globally distributed. Comparison was divided into 3 periods: 1991-1992, June 1993to April 1994, and 1995-2003, so as to understand SAGE II performance in dealing with different problematic periods, mainly volcanic eruptions and short events.…”
Section: Sage II Versus Haloementioning
confidence: 99%
See 1 more Smart Citation
“…Since both SAGE II and HALOE are carried on inclined-orbit satellites, occultation events are globally distributed. Comparison was divided into 3 periods: 1991-1992, June 1993to April 1994, and 1995-2003, so as to understand SAGE II performance in dealing with different problematic periods, mainly volcanic eruptions and short events.…”
Section: Sage II Versus Haloementioning
confidence: 99%
“…Over the years, several versions of SAGE II water vapor have been released and validated, most recently version 6.0 and 6.1 in 2000 and 2001. Various reviews of these versions indicated a consistent dry bias around the hygropause by as much as $40% [Chiou et al, 2000;Michelson et al, 2002;Kanzawa et al, 2002]. The retrieval is also strongly affected by volcanic aerosol contamination following El Chichón (1982) and Pinatubo (1991) and to a lesser extent, Ruiz (1985) and Kelut (1990) [Rosenlof et al, 2001;Kley et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…38 However, as discussed in Ref. 24 and illustrated in Fig. 15, a comparison of Version 2 and 3 results shows lower VMR for stratospheric water in this region for Version 3, while the VMRs for CH 4 are effectively unchanged.…”
Section: B H 2 O and H 2 O ϩ 2chmentioning
confidence: 82%
“…For illustrative purposes, profiles are compared from different spectral filters, but these were observed in similar air masses ͑as measured by potential temperature and a scaled potential vorticity; see Ref. 24 or 28͒. Version 3 profiles, both in Fig. 14 and in general, avoid the unrealistically low neartropopause H 2 O mixing ratios often seen in Version 2.…”
Section: B H 2 O and H 2 O ϩ 2chmentioning
confidence: 99%
See 1 more Smart Citation